Methodology for studying the functional conditions of athletes` skin - Zaborova, V. A.; Arzumanian, V. G.; Gurevich, K. G.; Terekhova, M. V. (International Journal of Sports Science, 2012)
The authors describe an unorthodox methodology for evaluating the functional skin conditions of athletes in various sports and offer their own findings. It is common knowledge that high physical stresses in modern sports affect the entire human organism, including skin conditions. As a specific of aquatic sports, athletes spend much time in water every day and expose their skin to chemical agents that are added to water to cleanse and disinfect it. The goal of this study was to develop a methodology for evaluating the quantity and quality of staphylococci, propionic bacteria, and fungi of genus Malassezia. Staphylococcal microflora was inoculated on the visibly healthy skin of 50 athletes engaged in aquatic sports: St. aureus was collected from 26 (54.7%) athletes pursuing aquatic sports, St. saprophyticus from 2 (3.2%) athletes, St. intermedius from 14 (25.2%) athletes, St. epidermidis from 6 (10.4%) athletes, and St. haemolyticus from 2 (4.8%) athletes. Among athletes engaged in non-aquatic sports, St. aureus was detected in 5 athletes (33.3%), St. saprophyticus in 1 athlete (6.7%), St. intermedius in 1 athlete (6.7%), and St. epidermidis in 8 athletes (53.3%). St. haemolyticus was not inoculated.